Gambaran indeks massa tubuh, tekanan darah, dan kadar gula darah sewaktu di Dusun Jaten, Sinduadi, Mlati, Sleman, DIY - Eri Yanuar Akhmad Budi Sunaryo; Rizky Endah Wuningsari; Sinthya Rasela; Trivena Putri; Vincentius Dennis Prabaniarga; Hamim Majdy Awliya Humani; Nur Wulan Wijayanti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Non-communicable diseases (NCDs) are chronic diseases that are not transmitted from person to person. Each year 41 million people die due to NCDs. From 1995 to 2007 (12 years), Indonesia has undergone an epidemiological transition in which deaths from NCDs increased, while deaths due to infectious diseases declined. Prevalence of NCDs in the Special Region of Yogyakarta (DIY) has also continued to increase in 2007-2013. We conducted research to obtain a description of body mass index, blood pressure, and random blood glucose in Jaten, Sinduadi, Mlati, Sleman, DIY as early screening for NCDs. This research was a retrospective study using data obtained from the records from a medical check-up done in a community service program on August 19, 2018. Data obtained included age, height, weight, blood pressure, and random blood glucose levels. A total of 96 people were screened. Most (72.9%) participants were adults (aged ≥ 20 years to ≤ 59 years). Results of the screening showed that 43% of participants were overweight or obese, 70% had hypertension, and 5.7% had the random blood glucose of ≥ 200 mg/dL. The percentage of obesity, hypertension, and diabetes mellitus in Jaten Hamlet are relatively high, indicating a need for long term education and intervention to decrease NCDs prevalence and complications.